The global budgets of organic hydroperoxides for present and pre-industrial scenarios. (June 2015) - Khan, M.A.H.; Cooke, M.C.; Utembe, S.R.; Xiao, P.; Morris, W.C.; Derwent, R.G.; Archibald, A.T.; Jenkin, M.E.; Percival, C.J.; Shallcross, D.E.
Abstract: The global 3-D chemistry-transport model, STOCHEM-CRI (Utembe et al., 2010), has been used to simulate the global distribution of organic hydroperoxides (ROOH) for both present day and pre-industrial scenarios. Globally, the formation of ROOH is solely from the reaction between RO2 and HO2, being more significant under NOx -limited conditions; here the self and cross reactions of RO2 and HO2 radicals dominate over their reaction with NO. The predominant global loss processes for ROOH are reaction with OH (95%) and by photolysis (4.4%) with a minor loss (<1%) by deposition, in the present day scenario. The associated global burden of ROOH in our model study is found to be 3.8 Tg. The surface distribution of ROOH shows a peak near the equator corresponding with higher photochemical activity and large (biogenic) VOC emissions. The simulated abundances of ROOH are comparable with those recorded in field campaigns, but generally show a tendency towards underestimation, particularly in the boundary layer. ROOH displayed seasonal cycles with higher concentrations during the summer months and lower concentrations during the winter months. The effects of including proposed HOx recycling schemes, including isomerisation of isoprene-derived peroxy radicals on the global budget of ROOH have also been investigated for the present and the pre-industrial environment. The present day simulations showed significant increases in CH3 OOH and ROOH (up to 80% and 30%, respectively) over tropical forested regions, due to a general increase in HO2 and RO2 levels in isoprene-rich regions at low NOx levels. In the pre-industrial scenario, the increases in CH3 OOH and total ROOH abundances are even larger, reflecting the more efficient operation of HOx recycling mechanisms at lower NOx levels. RCO3 H species contribute 40–50% of the global burden of ROOH; inclusion of HOx recycling mechanisms leads to an increase in these RCO3 H species but there is no discernible change in the remaining ROOH (ROOH–RCO3 H) burden. Highlights: The formation of ROOH from RO2 and HO2 is significant under NOx -limited conditions. The global burden of ROOH is found to be 3.8 Tg. ROOH peak near the equator having higher photochemistry and large VOC emissions. HOx recycling caused significant increases in ROOH over tropical forested regions.